Effect of street entrepreneurship transformation on small and medium enterprises performance - Aun, Isaac Iortimbir (Journal of Management, Economics, and Industrial Organization, 2022)
Street entrepreneurship is universal across the world but most common in less developed and emerging economies. The difficulties confronting roadside small business owners in Nigeria is connectivity to funding assistance, as a shortage of resources and metropolitan regulatory requirements and by-laws forced numerous SMEs to convert from licenced to unregistered enterprises. The study examines the impact of roadside entrepreneurship on the performance of SMEs, with a particular focus on operators in the Ilorin city. Since the study population is large and unknown Cochran sample size formula was used to determining the sample size of 385. A questionnaire was designed using structured questions to obtain primary data from respondents in Ilorin metropolis, Kwara State. A total of three hundred and eighty-five (385) copies of the questionnaire were administered, out of which three hundred and sixty-eight (368) were complete and found usable. The formulated hypotheses were tested using multiple regression analysis and correlation with the aid of SPSS v21. The study’s findings revealed that; street entrepreneurship transformative measures significantly affect SMEs’ profitability with an R2 value of .863, using correlation a strong positive relationship between this street entrepreneurship transformative measures and customer retention of SMEs with .932 having psychological and personal factors as the highest. Hence, the study concluded that all transformative measures of street entrepreneurship significantly affect profitability, customer and retention. Therefore, it was recommended that state government should consider giving out financial aids to street entrepreneurs and empowerment and assist the transformation of existing street entrepreneurship ventures into SMEs.